The Impact of Climate Change on the Heavy Rainfall and Extreme Temperatures (Bijar, Khalkhal, Zanjan, Qorveh and Miane Stations Sefidrood Basin) - Mojtaba Safavi; Hamid Moslemi; Marzeyh Rezai; Raheleh Darvishi (Nīvār)
The Occurrence of heavy rains and extreme events due to climate change has had devastating effects on the economic, social context. Therefore, studying the variability and behavior of heavy rainfall events and heavy rainfall is of particular importance. In this study, we investigated the impact of climate change on heavy rainfall and baseline temperatures (1989-2008) with a 20-year future period (2011-2030) for five stations in Bijar, Khalkhal, Zanjan and Mianeh in Sefidrood catchment. Heavy rainfall and maximum and minimum temperature values were generated using the LARS-WG model and climate scenario A1B, A2, B1 for the next 20 years. Brooks method was used to identify heavy precipitation and future temperatures of observation and future periods. According to this method, the upper temperatures and heavy rainfall of the base and future periods were divided into four groups of five years and were classified using statistical methods. The results show that the upper temperatures over the next few years will see an increase in the number of events, a downward trend but in terms of quantity, and the global warming trend in the minimum temperature indices will be higher than the maximum temperature related trend. . Heavy rainfall will be upward during the next period in Bijar and Khalkhal stations and in Zanjan, Qorveh and Middle stations.